INVENTARISASI JENIS UDANG DI PERAIRAN KAMPUNG NIPAH KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Febri Ramadhani Harahap; E. Harso Kardhinata; Hanifah Mutia ZNA (Universitas Medan Area, 2017)
Research on Inventory type of shrimp in the waters of Kampung Nipah Perbaungan Bedagai Serdang District of North Sumatra, aims to determine the types of shrimp. The method used in this research is descriptive by surveying the catch. Data collection was performed by a sample of shrimp fisherman catch sea and river waters Nipah home twon village it selp Nipah arrest shrimp sample. Results of research on the waters of the River and Sea waters found 13 species belonging to four families. The families that most species are Panaeidae, while families Squillidae has one endemic species in the waters of the Sea. The families that most species Palaemoidae, while families Atydae has one endemic species in the waters of the river.